Pupil-sparing third nerve palsies and hemiataxia: Claude's and reverse Claude's syndrome. (June 2016) - Bateman, James R.; Murty, Pavan; Forbes, Michael; Collier, Kisha Young; Tememe, Danoushka; Marchena, Octavio de; Powers, William J.
Highlights: The pupillomotor fascicular fibers are the most dorsal in the midbrain. Midbrain lesions can lead to pupil-sparing lesions by sparing these fibers. Ataxia ipsilateral to a third nerve palsy is a rare but recognized stroke syndrome. Abstract: We report two patients with midbrain infarction with pupil-sparing third nerve palsies and hemiataxia: one with contralateral ataxia (Claude's syndrome) and one with ipsilateral ataxia (which we refer to as reverse Claude's syndrome). We highlight the importance of a thorough neurologic evaluation with partial oculomotor palsies and describe, to our knowledge, the fourth account in the literature of a pupil-sparing third nerve palsy with ipsilateral cerebellar ataxia.